Secondary level students' perceptions of the teaching of Islamic studies at International Islamic School Malaysia (IISM) - Musah, Alhassan Musah (Kulliyyah of Education, International Islamic University Malaysia, 2016)
Despite the importance and increasing need for quality teaching methods and their positive impact on Islamic studies students of today, there is a perception that Islamic studies teachers are still using traditional teaching approaches to teach Islamic studies, such as memorization, drilling and rote learning. The aim of Islamic studies should be to produce good Muslims who are intellectually, mentally, emotionally and physically capable and so the teaching methods used by Islamic studies teachers need to promote this. This study set out to investigate the views of students on the methods used by their Islamic studies teachers at the International Islamic School Malaysia (IISM). The researcher used a quantitative research methodology to collect data at IISM Secondary by means of a survey. The sample comprised of 196 students from various levels and ethnic background. The findings of the study reveal that Islamic studies teachers in fact use a combination of both traditional and modern methods to teach Islamic subjects.